Design of 3 mm band Detector Indoor Calibration System - Wei Wang; Wangjie Chen; Li Wu; Shusheng Peng (Institute of Advanced Engineering and Science, 2014)
A 3mm band detector indoor calibration system is introduced in this paper, which is based on a STM32 embedded system. This embedded control system includes noise source control circuit, database circuit, a real time clock circuit, humidity and temperature sensor circuit, PS/2 interface circuit and SD card interface circuit. And a database, which contains radiation characteristics of metal targets, is built in this calibration system. Experiment results demonstrate that the indoor system could satisfy the requirement of 3 mm band detector calibration. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4501